DIPLOMASI EKONOMI INDONESIA DALAM MENINGKATKAN EKSPOR SARANG BURUNG WALET KE TIONGKOK PERIODE 2012-2018 - Tashya Maura, (2020)
East Asian countries have bright future market access for the Indonesian economy, one of them is China. China is a trade partner that bring positive influences on Indonesia's trade sector. In export-import, China is still the main destination country for Indonesia in marketing the commodities. One of the commodities that being marketed is swallow's nest. Indonesia is the largest swallow nest producer country and China is the country that dominate the world swallow nest market. But in the realization of the exports, Indonesia can't export directly to China. In addition, there are many administrative and technical obstacles to exporting swallow's nests themselves. With the discovery of these obstacles, it have an impact on the volume of swallow bird exports from Indonesia to China. This research will discuss how Indonesia's economic diplomacy in increasing swallow's nest exports to China on 2012 until 2018. This research uses a descriptive qualitative approach with data collection techniques in the form of interviews and literature study. The data obtained will be analyzed using economic diplomacy theory and the concept of non-tariff barriers to explain what efforts are being made by Indonesia to improve the swallow's nest export to China. The results of this study show that Indonesia's swallow nest exports to China have been shown to increase after diplomacy. Indonesia start with the form of bilateral meetings, negotiation and import exhibitions. This smooth diplomacy is supported by actors who play an important role in the trade sector.